Detection of Hepatitis B Genotypes in HBsAg & HBeAg Carriers - Khan, Salman; Madan, Molly (Journal of Biomedical and Pharmaceutical Research, 2018)
Objective:- Hepatitis B is noteworthy medical issues that may include the late continuation of liver cirrhosis and hepatocellular carcinoma. The present study aimed for the detection and diffrentiation of Hepatitis B virus HBsAg inactive non-replicative carriers, HBeAg-positive inactive replicative carriers, active carriers & HBeAg-negative chronic hepatitis B by Real Time PCR and their genotyping Methods: This research conducted on 245 positive for HBsAg, 118 (48.16 %) were male and 127 (51.84%) were female patients, which was performed in central research station labortory of Microbiology at netaji subhash Chandra Bose subharti Medical College and Hospital, Meerut Between march 2016 to November 2017 The sera were separated and screened for HBsAg by ELISA kit. Positive samples for HBsAg were tested for HBeAg ELISA kit and DNA Viral load then sequenced for genotying Results:. Of the 245 HBsAg Positive case 55 (1.12%) were HBeAg positive. In 16 PCR positive and HBV genotyping, In HBsAg inactive Non-Replicative 37.5% (n=6) genotype-B and 6.25% (n=1) genotype-A, In HBeAg inactive Replicative 12.5% (n=2) genotype-B and 12.5% (n=2) genotype-A and In HBeAg Active Chronic Hepatitis B 18.75% (n=3) genotype-B and 12.5% (n=2) genotype-A were detected Conclusions: Management strategy, using HBsAg, HBeAg and HBV DNA viral load, seems adequate for the confirmation and diffrentiation of Hepatitis B virus inactive, active carriers & HBeAg-negative chronic hepatitis B patients and genotype B was more prevalent in comparission to genotype A. Distribution of carriers & genotypes, help physicians to prescribe proper antiviral/interferon therapy according to current genotyping pattern in this region Keywords: Hepatitis B virus, Carrier State, HBsAg, HBeAg, RT-PCR